2016
DOI: 10.1182/blood-2015-08-667485
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase gene therapy rescues telomere length, bone marrow aplasia, and survival in mice with aplastic anemia

Abstract: Key Points• Telomerase gene therapy in a mouse model of aplastic anemia targets the bone marrow and provides increased and stable telomerase expression.• Telomerase expression leads to telomere elongation and subsequently to the reversal of aplastic anemia phenotypes.Aplastic anemia is a fatal bone marrow disorder characterized by peripheral pancytopenia and marrow hypoplasia. The disease can be hereditary or acquired and develops at any stage of life. A subgroup of the inherited form is caused by replicative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 42 publications
2
44
0
3
Order By: Relevance
“…However, murine models have shown that reactivation of telomerase is able to rescue homeostasis across different tissues in telomerase-mutant mice (Bar et al., 2016, Jaskelioff et al., 2011). We therefore asked whether telomerase reactivation via genetic correction could restore human definitive hematopoietic potential in DC hESCs.…”
Section: Resultsmentioning
confidence: 99%
“…However, murine models have shown that reactivation of telomerase is able to rescue homeostasis across different tissues in telomerase-mutant mice (Bar et al., 2016, Jaskelioff et al., 2011). We therefore asked whether telomerase reactivation via genetic correction could restore human definitive hematopoietic potential in DC hESCs.…”
Section: Resultsmentioning
confidence: 99%
“…It may occur at any age, however young individuals (age 10-25 years) and the elderly (>60 years) are the most prone. No significant differences in gender have been noted [1]. AA incidence in the United States and Europe is below 2.5/million, while the incidence of AA in Asia is 2-3 times higher [2,3].…”
Section: Introductionmentioning
confidence: 87%
“…Christian Bar et.al administered adeno-associated virus (AAV) 9 gene therapy vectors carrying the telomerase TERT gene to AA mouse models that had short telomere length. They found that telomerase activation reversed AA and improved survival [1]. These findings indicated that telomerase activation could be a novel therapeutic strategy to treat AA associated with short telomere length.…”
Section: Telomeresmentioning
confidence: 93%
See 1 more Smart Citation
“…Por otra parte, la activación de la telomerasa mediante el uso de vectores en terapia génica de virus adenoasociados que llevan el gen Tert de la telomerasa en modelos de ratones independientes de anemia aplásica debido a telómeros cortos, encontró que una dosis alta de este vector se dirige al compartimento de la médula ósea, incluidas las células madres hematopoyéticas, mejorando la supervivencia, produciendo un aumento significativo de la longitud de los telómeros en las células de sangre periférica y de la médula ósea, así como un mejor conteo sanguíneo. Estos hallazgos indican que la terapia génica con telomerasa representa una estrategia terapéutica novedosa para tratar la anemia aplásica provocada o asociada con telómeros cortos (9,15).…”
Section: Tratamientounclassified